Effect of dietary supplementation of probiotic on performance and intestinal microflora of Chinese soft‐shelled turtle (Trionyx sinensis). (28th June 2014) - Zhang, X.; Peng, L.; Wang, Y.; Liang, Q.; Deng, B.; Li, W.; Fu, L.; Yu, D.; Shen, W.; Wang, Z.
Abstract This experiment was conducted to study the effect of dietary supplementation of probiotic on performance and intestinal microflora of Chinese soft‐shelled turtle. Healthy Chinese soft‐shelled turtles (6000 pieces with average weight of 5 g) were selected and randomly divided into two groups: control and treatment with three replicates each. The control was fed on normal basal diet, whereas treatment was fed on basal diet supplemented with 1 × 108 cfu.g−1Bacillus subtilis preparation. The results showed that the final mean weight of treatment (265.84 ± 3.48 g) was significantly higher (P < 0.05) than that of control (240.45 ± 4.32 g). There was significant difference (P < 0.05) in FCR, and DGs were obtained in probiotics fed group as compared to control. The level of sucrase, maltase, amylase, lipase and ATPase of treatment was significantly higher (P < 0.05) than that of control. Pyrosequencing showed that the dietary supplementation of probiotic Bacillus strain decreased microbial diversity. Phylum Firmicutes was dominant in both groups. Compared with the control, Firmicutes was increased, while others were decreased in treatment group. The results indicated that dietary supplementation of probiotic can improve growth performance, digestibility and intestinal microflora in Chinese soft‐shelled turtle.